UJI EFEKTIVITAS BOOKLET BERBAHASA DAERAH DAN METODE CERAMAH TERHADAP PENGETAHUAN REMAJA TENTANG ROKOK (Studi di MTs Aswaja Pontianak dan SMP Assalam Pontianak) - Iskandar, Iskandar; Ridha, Abduh; Hernawan, Andri Dwi (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2015)
Background: The high number of smokers among teenagers Indonesia increasingly alarming, the data indicates that the increase occurs every year. the importance of self-protection against non adolescents should be done more seriously by the government, so that we are not getting a lot of teenagers who behave smoke. Health promotion is one of the steps that need to be given to adolescents. Selection of media in health promotion should also be appropriate in order to facilitate the message delivered to teenagers. One medium that is suitable for teenagers is the booklet, because booklet may contain more material and interesting shapes dibandingka with other health promotion media.Aim : This study aimed to examine the effectiveness of the local language booklet and lecture method in increasing knowledge about smoking in adolescents.Method : This research uses experimental design. Samples are 69 respondents (34 treated and 25 controls) were taken using simple techniques proporsive sampling. Using repeated ANOVA test with a confidence level of 95%.Result : The results showed there were no differences in knowledge significantly in pretest between the booklet and lecture (p value = 0.153), there are differences in knowledge significantly between groups booklets and lectures on the posttest 1 (p value = 0.000), There was an increase in knowledge on the group booklet between pretest and posttest 1 (p value = 0.000). An increase knowledge on the booklet group between posttest 1 and posttest 2 (p value = 0.049). increased knowledge of the lecture group between pretest and posttest (p value = 0.000). Value the effectiveness of both methods was calculated using the formula eta squared result in a lecture 0.73 and 0.47 on the lecture method, which means that both methods have great effectiveness in increasing knowledge about smoking in adolescents.Suggestion: Suggested to Pontianak City Health Department to improve health promotion against teenagers using media health promotion in the form of booklets speaking regions, because of the results of the study show the effectiveness of the booklet reached 73% while 47% lectures For many teens are exposed to information about smoking.Keywords : Booklet Regional Languages, Methods Lecture